2019
DOI: 10.1101/684217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The chromatin remodeler SMARCD3 regulates cell cycle progression and its expression predicts survival outcome in ER+ breast cancer

Abstract: Chromatin remodeling plays an essential role in regulating transcriptional networks and timing of gene expression. Chromatin remodelers such as SWItch/Sucrose Non-Fermentable (SWI/SNF) harbor many protein components, with the catalytic subunit providing ATPase activity to displace histones along or from the DNA molecules, and associated subunits ensuring tissue specificity and transcriptional or cotranscriptional activities. Mutations in several of the SWI/SNF subunits have been linked to cancer. Here, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…SMARCD3, also known as BAF60C, is a member of the SWI/SNF chromatin remodeling complex and has been implicated in various cancers, exerting diverse roles depending on the specific cancer type [ 27 , 28 , 29 , 30 ]. In pancreatic cancer, SMARCD3 has been associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SMARCD3, also known as BAF60C, is a member of the SWI/SNF chromatin remodeling complex and has been implicated in various cancers, exerting diverse roles depending on the specific cancer type [ 27 , 28 , 29 , 30 ]. In pancreatic cancer, SMARCD3 has been associated with a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, SMARCD3 has been linked to promoting tumor growth and invasion in pancreatic cancer cells. Conversely, in uterine and breast cancers, SMARCD3 acts as a tumor suppressor [ 28 , 30 , 34 ]. Studies have shown that loss of SMARCD3 expression is associated with aggressive tumor behavior, increased metastasis, and poorer patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation